1990
DOI: 10.1111/j.1651-2227.1990.tb17306.x
|View full text |Cite
|
Sign up to set email alerts
|

Medulloblastoma in Nordic Children. I

Abstract: ABSTRACT. The average annual incidence of histologically verified medulloblastomas was 5.4×10‐6 among all 4.9 million Nordic children younger than 15 years from 1968 to 1977. The ratio between boys and girls was 2:1. The incidence had no clear seasonal variation and it peaked at 3 to 4 years of age at onset. The rate of survival after 5 years was 17.4%, equal for boys and girls, but highest in the older age groups. Tumor growth accounted for most deaths with lack of local control in 88% of 112 children autops… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
3
0

Year Published

1990
1990
2003
2003

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 24 publications
2
3
0
Order By: Relevance
“…The typical lag time between symptom and diagnosis improved after the 1954 to 1964 period but has not changed since. In results similar to ours, Clausen et al (1990) found that diagnostic delay varied between 1 and 42 months with a median of 2 months. They also failed to find any relationship between the length of the diagnostic delay and subsequent survival.…”
Section: Incidencesupporting
confidence: 88%
See 3 more Smart Citations
“…The typical lag time between symptom and diagnosis improved after the 1954 to 1964 period but has not changed since. In results similar to ours, Clausen et al (1990) found that diagnostic delay varied between 1 and 42 months with a median of 2 months. They also failed to find any relationship between the length of the diagnostic delay and subsequent survival.…”
Section: Incidencesupporting
confidence: 88%
“…It represents 8% of all solid tumours in children and 20% of CNS tumours of childhood (Blair and Birch 1994). The overall incidence rate of 4.5 cases per million child years is similar to that reported in studies from other areas in the UK (Stevens et al 1991, Thorne et al 1994) and other countries (Clausen et al 1990, Gjerris et al 1998.…”
Section: Incidencesupporting
confidence: 77%
See 2 more Smart Citations
“…The follow-up study occurred in [1982][1983][1984][1985][1986]. Details have been given elsewhere (3,4).…”
Section: Methodsmentioning
confidence: 99%